Red Hangover : Legacies of Twentieth-Century Communism - Ghodsee, Kristen Rogheh, 1970- (Book collections on Project MUSE., 2017)
Kristen Ghodsee examines the legacies of twentieth-century communism on the contemporary political landscape twenty-five years after the Berlin Wall fell, reflecting on the lived experience of postsocialism and how many ordinary men and women across Eastern Europe suffered from the massive social and economic upheavals in their lives after 1989.